FILOSOFI NABI IBRAHIM MENCARI TUHAN MELALUI BULAN, BINTANG DAN MATAHARI - Edi Sumanto (Universitas Islam Negeri Fatmawati Sukarno, 2018)
If the nature of the horizon above is observed, which also shows the sun, moon, stars and so on, so does the earth with all its contents in the form of humans, animals, plants and solid objects, there is a close relationship with the complicated balance that smoothes the arrangement between the various colors of nature and that strengthen each other’s circumstances. Everything is a sign and proof of the form of Allah Almighty. In addition to showing the existence of the Substance of Allah SWT also proves the oneness and to His Almighty created it. It seems not to be imagined at all in anyone’s mind that these objects occur without anyone creating as well as it is impossible to imagine that something created no one made it.